Isolation and Characterization of Phenanthrene-Degrading Bacteria from PAHs Contaminated Mangrove Sediment of Thane Creek in Mumbai, India. (1st January 2019) - Sukhdhane, K. S.; Pandey, P. K.; Ajima, M. N. O.; Jayakumar, T.; Vennila, A.; Raut, S. M.
ABSTRACT: Polycyclic aromatic hydrocarbons (PAHs), including phenanthrene, are commonly found as pollutants in soils, estuarine, and sediments, as well as in terrestrial and other aquatic ecosystems. In this context, the phenanthrene-degrading bacteria were isolated and characterized in contaminated mangrove surface sediment, on the coast of Thane Creek, Mumbai, India by enrichment method, using phenanthrene as the sole source of carbon and energy. The phylogenetic diversity of the isolates were evaluated by 16S rRNA gene analysis and characterized as Bacillus mojavensis strain KSS001, Bacillus firmus strain KSS002, Bacillus flexus strain KSS003, Bacillus vietnamensis strain KSS004, and Bacillus amyloliquefaciens strain KSS005. Each isolate was grown on the phenanthrene up to 100 mg/L and the biodegradation ability was evidenced using a gas chromatography–flame ionization detector. Further, the mean value of phenanthrene degradation by 5 bacterial isolates after incubation in mineral salt medium for 7 days was 63% at 100 mg/L. The study reports that mangrove sediments of Thane Creek, Mumbai, contain a diverse population of phenanthrene-degrading bacteria that have the potential and capability to degrade PAHs contaminated sites, and are consequently recommended for bioremediation.